مكانة القيم الأخلاقية في ترشيد العمل السياسي - موفق, نبيل (revue mofakir, 2018)
In this Article, we discuss the inter- action between political activities and morals ; to sort out and clarify the necessary dimentions of the moral responsability that the political officias need to behave with in all classes ; either leadership or elector/ elected. There is no doubt that morals have a specific value in the political action to rise the planned objectives for the benefit of the nation and the citizen, protection of his property and the best labour management. This labour is founded on the citizen himself since he is the basic source to fulfil it succesfully. What urged me to write this topic , is all what is noticed in the political field nowadays, Once there is an electoral term, either locally or on the national level ; such as the disapearence of morals and the pure values of the political chalange, which led to the los of loyalty and shifted to enmity and hatred. All that led also to nearly wasting goals and finalities of the political action. In order not to keep meaning of morals in the political action just as ink on paper, it is necessary then to be sesibilized , revising its theories and perspectives , highliting its constituents ; hence predicting its fruits and results. That’s what i ment infact in my topic. On the light of all that, I confirm the role of the moral values in good governance and evaluate its basis, such as the scientific management, the daily life experience and the political culture.